2020
DOI: 10.1681/asn.2020030323
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between AKI and CKD in Patients with Type 2 Diabetes: An Observational Cohort Study

Abstract: BackgroundThere are few observational studies evaluating the risk of AKI in people with type 2 diabetes, and even fewer simultaneously investigating AKI and CKD in this population. This limits understanding of the interplay between AKI and CKD in people with type 2 diabetes compared with the nondiabetic population.MethodsIn this retrospective, cohort study of participants with or without type 2 diabetes, we used electronic healthcare records to evaluate rates of AKI and various statistical methods to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 32 publications
2
60
0
Order By: Relevance
“…14 A recent observational study by Hapca et al concluded from their cohort of patients that in the absence and presence of CKD, the rates of AKI were nearly 5 times and 2 times, respectively, for patients with diabetes compared to the control groups. 16 Mechanisms postulated to explain the susceptibility of DM to AKI include endothelial dysfunction due to upregulation of vasoconstrictor endothelin −1 (ET-1), downregulation of nitric oxide production, 25,26 proximal tubular injury secondary to upregulation of inflammatory cytokines like tumour necrosis factor (TNF)-α, interleukin (IL)-1, IL-6, maladaptive repair process which causes scarring and tubulointerstitial fibrosis leading to CKD progression and ESKD. 27,28 We studied the incidence of AKI in our cohort as most of the observational studies included incidences of AKI only in hospitalized patients, critically ill, 11 elderly, 29 postsurgical patients 30 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14 A recent observational study by Hapca et al concluded from their cohort of patients that in the absence and presence of CKD, the rates of AKI were nearly 5 times and 2 times, respectively, for patients with diabetes compared to the control groups. 16 Mechanisms postulated to explain the susceptibility of DM to AKI include endothelial dysfunction due to upregulation of vasoconstrictor endothelin −1 (ET-1), downregulation of nitric oxide production, 25,26 proximal tubular injury secondary to upregulation of inflammatory cytokines like tumour necrosis factor (TNF)-α, interleukin (IL)-1, IL-6, maladaptive repair process which causes scarring and tubulointerstitial fibrosis leading to CKD progression and ESKD. 27,28 We studied the incidence of AKI in our cohort as most of the observational studies included incidences of AKI only in hospitalized patients, critically ill, 11 elderly, 29 postsurgical patients 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with a sepsis-associated AKI showed greater decline in eGFR which was in stark contrast compared to other etiologies. The prior studies 16 , 31 , 32 done on patients with diabetes mellitus and diabetic kidney disease did not study the causes for AKI. We acknowledge that sometimes there could be an overlap in the causes leading to AKI which can make it difficult to pinpoint an exact etiology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Type 2 diabetes mellitus (T2DM) is a major cause of chronic kidney disease (CKD) and kidney failure. Small trials have suggested that T2DM might also be a risk factor for AKI and a large retrospective cohort study conducted by the BEAt-DKD consortium in Scotland further supports its potential as an independent risk factor in the absence of CKD 3 . In this study, 16,700 participants (9,417 with T2DM and 7,283 controls without T2DM) were followed for a median of 8.2 years.…”
mentioning
confidence: 91%